2018
DOI: 10.1093/cid/ciy473
|View full text |Cite
|
Sign up to set email alerts
|

Breakthrough Invasive Mold Infections in the Hematology Patient: Current Concepts and Future Directions

Abstract: Although the widespread use of mold-active agents (especially the new generation of triazoles) has resulted in reductions of documented invasive mold infections (IMIs) in patients with hematological malignancies and allogeneic hematopoietic stem cell transplantation (HSCT), a subset of such patients still develop breakthrough IMIs (bIMIs). There are no data from prospective randomized clinical trials to guide therapeutic decisions in the different scenarios of bIMIs. In this viewpoint, we present the current s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
108
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 83 publications
(122 citation statements)
references
References 81 publications
2
108
0
2
Order By: Relevance
“…In contrast, our patient's initial lesions developed despite normal ANC for 12 days prior, and the biopsy confirmed that these same lesions were due to IF. This case further highlights the complex epidemiology of breakthrough invasive mold infections occurring in immunosuppressed hematological patients …”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…In contrast, our patient's initial lesions developed despite normal ANC for 12 days prior, and the biopsy confirmed that these same lesions were due to IF. This case further highlights the complex epidemiology of breakthrough invasive mold infections occurring in immunosuppressed hematological patients …”
Section: Discussionmentioning
confidence: 83%
“…There are several reports of immunosuppressed patients developing severe fungal infections despite antifungal prophylaxis . Fluconazole and echinocandins are common well‐tolerated choices for antifungal prophylaxis in patients with ALL; echinocandins, as opposed to fluconazole, have some activity against Aspergillus .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breakthrough fungal infections in patients with neutropenia receiving prophylactic voriconazole are commonly observed, with trough concentrations < 1 μg/mL associated with progressive fungal disease. 6,8,16,21,22 Epidemiology studies have shown that drug-resistant Aspergillus and non-Aspergillus molds are commonly observed among those with breakthrough infections. 21,22 Prolonged exposure to suboptimal voriconazole concentrations may mechanistically promote acquired resistance and selection of subpopulations with primary resistance.…”
Section: Discussionmentioning
confidence: 99%
“…6,8,16,21,22 Epidemiology studies have shown that drug-resistant Aspergillus and non-Aspergillus molds are commonly observed among those with breakthrough infections. 21,22 Prolonged exposure to suboptimal voriconazole concentrations may mechanistically promote acquired resistance and selection of subpopulations with primary resistance. [23][24][25] The CYP2C19*17 allele is a risk factor for low voriconazole concentrations and can affect ~ 25% of patients.…”
Section: Discussionmentioning
confidence: 99%